Physical parametric analysis of the terahertz photonic crystal cavities substrate microstrip antenna on the performances / Nor Hidayah Roslan - Roslan, Nor Hidayah (2017)
This thesis study about the photonic crystal cavity (PCC) as a substrate and microstrip patch antenna in Terahertz (THz) frequency has been simulated and analyzed. The objectives are to simulate and analyze the performances changes when the parameters of PCC and microstrip patch antenna are varied. THz PCC substrate microstrip antenna is a most simple way to generate THz frequency. However, they are limited studies that have been done in terms of its fundamental physical analysis. Therefore, this parametric analysis is proposed. The design of the PCC and rectangular microstrip patch antenna of the electromagnetic spectrum on the 2-D photonic crystal was simulated using Computer Simulation Technology (CST) CAD Package. The effective permittivity, 2.08 with host material PTFE and copper annealed at 0.6THz. We varies the radius of the via, thickness of PCC, spacing between via and the width of the PCC. For the patch antenna the thickness and the material are varied. The performances are monitored through its resonant frequency, S-parameter return loss (SI 1), Gain, Radiation pattern, E-field H-filed and current density.